Perkembangan kelekatan anak = The Development of Children Attacment - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
There are many factors that influence infants attachment behavior and development. One of them was child rearing practices (Ainsworth, 1973